Effects of pH Shift and Agitation Speed on Chlorophyll Biosynthesis in Heterotrophic Culture of Chlorella - ASANO, MASAKI; NISHIYAMA, YUKITAKA; FUNAHASHI, HITOSHI; NAKAO, KATSUMI (KAGAKU KOGAKU RONBUNSHU, 1999)
Chlorella sp., which has been used for industrial biomass production, was cultured under a heterotrophic condition. When pH was kept at 6.0 during the initial period of the culture, corresponding to logarithmic growth of cell, and thereafter shifted to 8.0, the instantaneous specific production rates of chlorophyll (CHL) throughout the culture were maintained at relatively high values. This pH shift pattern was proposed as the optimum one. The maximum CHL content under the optimum pH shift, however, was only 1.28 W/W % at the agitation speed of 600 r.p.m.. On the other hand, low agitation speeds less than 300 r.p.m. were more favorable for CHL biosynthesis. The maximum CHL content reached 3.1 W/W % at the agitation speed of 250 r.p.m.. This value was about 2.4 times higher than that in the case of 600 r.p.m.. It was suggested that the effect of agitation speed on CHL biosynthesis depended on the existence of a period lacking oxygen supply. Though the maximum CHL content reached also about 3 W/W % under the constant pH value of 6.0 at agitation speed of 250 r.p.m., the specific production rate of CHL during the middle period of the culture was 0.54 × 10 kg/ (kg dry cell·h), and about 70 % of that in the case of the optimum pH shift. This result revealed that CHL biosynthesis in the heterotrophic culture of Chlorella sp. was carried out more efficiently under both the optimum pH shift and the agitation speed of 250 r.p.m..